«Texel density» в індустрії комп’ютерних відеоігор - Маслік, Д. Є. (ХНУРЕ, 2025)
This article explores the concept of texel density in 3D graphics and its importance in game development. It covers the fundamentals of texel density, how it affects texture quality, and the role of UV mapping in achieving consistent detail across 3D models. The paper discusses methods for adjusting UV islands to maintain uniform texel distribution and explains how different platforms, from mobile games to VR, require varying texel densities. Additionally, it examines the impact of texel density on performance optimization and visual consistency.
Keywords: «Texel density»; індустрія комп’ютерних відеоігор